South African parents' perceptions of online learning during the COVID-19 pandemic - Naidoo, Mikaela Kayleen (University of the Witwatersrand, Johannesburg, 2024)
The COVID-19 pandemic caused substantial disruptions in daily life, with the education system being significantly affected. Schools were shut down due to lockdown regulations and South Africa’s unequal education system was exposed. While numerous studies have examined the experiences of teachers and learners, few have focused on parents, especially within the South African context. Therefore, through a qualitative approach, this study explored South African parents' perceptions and experiences of online learning during the COVID-19 pandemic. The sample consisted of 12 parents with children in Grades 5 to 10, attending private mainstream schools in Johannesburg. Data was collected through online interviews and through a thematic analysis of the data, four core themes were identified. These include: The Advantages of Online Learning During the Pandemic; The Challenges Related to Online Learning During the Pandemic; Coping Under Pressure; and Factors Influencing Learner Motivation. The findings showed that there were both advantages and disadvantages to online learning. It also highlighted the vital role parents have in online learning when compared to face-to-face learning. The findings of this study have implications for the professional development of teachers, emphasizing the need for training in online teaching methods that incorporate parents' insights given their first-hand experiences with online learning. The findings also highlight the need to ensure learners have access to digital devices in order to engage effectively in online learning.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Education in Educational Psychology (by course work and research report)to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: Online Learning; COVID-19; Parent Experiences; UCTD; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure